Venoarterial extracorporeal membrane oxygenation for vasoplegic shock after treprostinil refill of an implanted intravenous pump: a case report - Valencia, Lucía; López, Sergio; Olivas, Ana; Becerra, Ángel; Alemán-Segura, María Desirée; Évora-García, Marta; Ojeda, Nazario; Cabrera, Leonardo; Rodríguez-Pérez, Aurelio; Pérez-Peñate, Gregorio (Frontiers in Cardiovascular Medicine, 2024)
Introduction Venoarterial extracorporeal membrane oxygenation (ECMO) is a rescue therapy that can stabilize patients with hemodynamic compromise. Indications continue to evolve, including drug overdose. However, the indication merely for vasoplegic shock following drug overdose is controversial. Case summary We report a case of a 57-year-old male with high-risk idiopathic pulmonary arterial hypertension treated with upfront triple combination therapy (sildenafil, bosentan, and intravenous treprostinil infusion via subcutaneous abdominal implantable pump). In one of the refills of the drug reservoir, accidental administration of 1 months's supply of treprostinil (200 mg) into the subcutaneous tissue occurred, causing refractory vasoplegic shock. He required urgent VA-ECMO for 96 h, surviving to discharge 28 days later. Discussion Treprostinil poisoning is rare due to its less frequent use but is life-threatening. ECMO may be considered in vasoplegic shock due to overdose of vasodilatory medication. It allows organ perfusion to be maintained, with the knowledge that recovery is as rapid as drug elimination.